Akibat Hukum Penetapan Itsbat Nikah terhadap Perkawinan Tidak Tercatat: (Studi di Kabupaten Aceh Singkil) - Muhammad Radhi Aulia; Zamakhsyari bin Hasballah Thaib; Rosnidar Sembiring (CV Rewang Rencang, 2025)
Unregistered marriages create legal uncertainty for Indonesian society, particularly regarding marital status and civil rights. This research analyzes the legal consequences of itsbat nikah (marriage validation) decisions on unregistered marriages in Aceh Singkil Regency using descriptive analytical methods and empirical juridical approaches. The research findings indicate that unregistered marriages are caused by local cultural factors, economic conditions, geographical factors, and weak administrative roles. The itsbat nikah process at Mahkamah Syar'iyah Singkil follows Religious Court Law provisions, resulting in declaratory decisions that provide legal basis for registration at KUA (Office of Religious Affairs), state administrative recognition, and civil rights guarantees, although the status of children born before itsbat requires separate determination. The research recommends improving marriage registration socialization, inter-institutional coordination, and public awareness to avoid legal problems.